(untitled) (Conference Zone, 2022)
Building a knowledge economy is a key factor in the modern economic growth of any country. This will require innovative growth in the real sector of the economy, which in turn will require more and more investment from year to year. Today, Uzbekistan is moving away from outdated methods of managing the economy to advanced methods such as innovation management, project management and implementing a new concept of capital market development by increasing its integration into the world market.